Laser-based hybrid process for machining hardened steels - Raghavan, Satyanarayanan (Georgia Institute of Technology, 2013)
Cost-effective machining of hardened steel (>60 HRC) components such as a large wind turbine bearing poses a significant challenge. This thesis investigates a new laser tempering based hybrid turning approach to machine hardened AISI 52100 steel parts more efficiently and cost effectively. The approach consists of a two step process involving laser tempering of the hardened workpiece surface followed by conventional machining at higher material removal rates using lower cost ceramic tooling to efficiently cut the laser tempered material. The specific objectives of this work are to: (a) study the characteristics of laser tempering of hyper-eutectoid 52100 hardened steel, (b) model the laser tempering process to determine the resulting hardness, and (c) conduct machining experiments to evaluate the performance of the laser tempering based hybrid turning process in terms of forces, tools wear and surface finish. First, the microstructure alterations and phase content in the surface and subsurface layers are analyzed using metallography and x-ray diffraction (XRD) respectively. Laser tempering produces distinct regions consisting of - a tempered white layer and a dark layer- in the heat affected subsurface region of the workpiece. The depth of the tempered region is dependent on the laser scanning conditions. Larger overlap of laser scans and smaller scan speeds produce a thicker tempered region. Furthermore, the tempered region is composed of ferrite and martensite and weak traces of retained austenite (~ 1 %). Second, a laser tempering model consisting of a three dimensional analytical model to predict the temperature field generated by laser scanning of 52100 hardened steel and a phase change based hardness model to predict the hardness of the tempered region are developed. The thermal model is used to evaluate the temperature field induced in the subsurface region due to the thermal cycles produced by the laser scanning step. The computed temperature histories are then fed to the phase change model to predict the surface and subsurface hardness. The laser tempering model is used to select the laser scanning conditions that yield the desired hardness reduction at the maximum depth. This model is verified through laser scanning experiments wherein the hardness changes are compared with model predictions. The model is shown to yield predictions that are within 20 % of the measured hardness of the tempered region. Using the laser scanning parameters determined from the laser tempering model, cutting experiments using Cubic Boron Nitride (CBN) tools and low cost alumina ceramic tools are conducted to compare the performance of laser tempering based hybrid turning with the conventional hard turning process. The machining experiments demonstrate the possibility of higher material removal rates, lower cutting forces, improved tool wear behavior, and consequently improved tool life in the laser tempering based process. In addition, the laser tempered based hybrid turning process produce is shown to yield lower peak-to-valley surface roughness height than the conventional hard turning process. Furthermore, it is found that lower cost ceramic tools can be used in place of CBN tools without compromising the material removal rate.